Filozofia po góralsku wobec Aten Roztocza - Obirek, Stanisław (Humaniora. Czasopismo Internetowe, 2024)
Józef Tischner (1931–2000) often wove expressions from the mountain dialect into his texts and lectures. He was convinced that the highland mentality concealed authentic philosophical thinking, and was especially fascinated by the highlanders attachment to freedom (śleboda). The culmination of these fascinations was a book written in highland dialect, Philosophy in Highlander (1997), which is regarded as Tischner’s most original achievement. Less well known is the philosophical project, still in statu nascendi, of philosopher and theologian Tadeusz Guz (b. 1959) to establish a philosophical center in Roztocze, which he called the Athens of Roztocze. Although Guz’s project is in its beginning, one can see in it a certain idea of synthesizing many philosophical and theological traditions. The purpose of this article is to juxtapose these two ideas as attempts to incorporate philosophical thinking into a local context.